A New Species of the Scinax perpusillus Group (Anura: Hylidae) from Espírito Santo, Brazil - Faivovich, Julián (2010)
A new species of the Scinax perpusillus group is described from southern Esprito Santo, Brazil. It differs from the other ten species of the group in having the dorsum of body and limbs densely covered by prominent granules (smooth or with scattered irregular warts in all other species of the group) and in lacking any trace of markings on dorsum, inguinal region, and hidden surfaces of hindlimbs (present in all other species of the group). The new species is known only from the type locality. Unpigmented nuptial pads, never previously reported for the group, are present in all studied species (nine of eleven included in the group). Inguinal glands are easily visible in the new species, S. alcatraz, and S. littoreus.